Exploring The Effectiveness Of Forgiveness Therapy In Enhancing Self-Forgiveness Among Adult Children Of Divorced Parents: A Case Study - Mariyani, Devi; Yulia Ayriza; Farida Harahap (The Eastasouth Journal of Social Science and Humanities, 2025)
This study investigates the effectiveness of forgiveness therapy in enhancing self-forgiveness among women affected by parental divorce. The subject, a 26-year-old female entrepreneur, was struggling with self-blame, particularly following the trauma of her parents' divorce. The research applied the Heartland Forgiveness Scale (HFS) to assess self-forgiveness levels before and after a structured six-session intervention. The forgiveness therapy, based on Enright’s model, involved phases such as uncovering pain, decision to forgive, working through emotions, and deepening the process. Data collected showed a significant improvement in the client’s ability to forgive herself, as evidenced by her higher scores on the HFS after completing the therapy. The study reveals the critical role of forgiveness interventions in addressing emotional pain, particularly self-blame, in the aftermath of traumatic life events like divorce. Findings also highlight the therapeutic potential of structured forgiveness programs to improve psychological well-being and life satisfaction. This case study contributes to the growing body of literature on forgiveness therapy and its application in trauma recovery.